The use of blogs as reflective learning tools for placement students - Wolf, Katharina (School of Marketing, Curtin Business School, 2009)
This paper reviews the effectiveness of web logs (blogs), or online journals, within the context of a compulsory, final year placement unit for public relations students. The key goal behind the use of Web2.0 technology was to encourage ongoing, reflective practice via an exchange between students; thereby limiting feelings of isolation, commonly reported during the course of this individual tuition unit (ITU). Secondary objectives were to encourage exchange between participating students based at different, on- and offshore campuses, therefore integrating an international perspective and insight into best industry practice. Online journals have their shortcomings, particularly from an administrative point of view. However, the results indicate that the introduction of the Reflective Blog can be described as a success, particularly in the context of an individual tuition unit, by effectively shifting the focus away from textbook- and teacher-centric education, to interactive, peer to peer learning opportunities.